APPLICATION OF PROJECT BASED LEARNING IN ENGLISH TEACHING DURING A PANDEMIC AT AL AZHAAR ELEMENTARY SCHOOL - Dina Kartikawati (STKIP PGRI Trenggalek, 2020)
On March 2020, director General of Wealth Health Organization establishes the corona virus outbreak as pandemic. This condition affects the world in all aspects, including in education. The schools close and students have to learn independently at home. This condition is not so problematic for developed countries but for developing countries as Indonesia, this condition brings enormous effect as most of teachers and students do not ready with this condition. They have to change the old system or face to face learning system or offline learning system into distance learning or online. Even there are so many applications that can be used to conduct online learning, they still do not familiar with them and cannot operate them. It makes teachers use familiar application to teach by project based learning.